Disparities in activity levels and learning ability between Djungarian hamster (Phodopus sungorus) and Roborovskii hamster (Phodopus roborovskii). (20th July 2016) - Ikeda, Hiromi; Nagasawa, Mao; Yamaguchi, Takeshi; Minaminaka, Kimie; Goda, Ryosei; Chowdhury, Vishwajit S.; Yasuo, Shinobu; Furuse, Mitsuhiro
Abstract: The Djungarian hamster and the Roborovskii hamster belong to the same genus of Phodopus . However, the Djungarian hamster is tame and shows sedative behavior, while Roborovskii hamster is not tame and shows high levels of locomotor activity. Hyperactivity occurs in animals with tameless behavior. Tameness or tamelessness behavior is very important because tameness helps for breeding and controlling as well as it enables a strong human‐animal bond. In the present study, we examined the relationships between activity levels and cognitive function in Djungarian and Roborovskii hamsters. Three types of behavioral tests were performed to analyze their activity levels, memory and leaning ability. The levels of L‐ and D‐amino acids and monoamines in the brain were then determined. Roborovskii hamsters showed significantly higher locomotor activity than Djungarian hamsters. Memory ability was not significantly different between the two hamsters, but Roborovskii hamsters showed lower learning ability. Brain levels of D‐serine which is related to enhancement in memory and learning ability, were significantly higher in Djungarian hamsters, but the reverse was true for brain dopamine and serotonin levels. These results suggest that these differences in brain metabolism may be related to the behavioral differences between the two hamsters.